The second best exotic Marigold Hotel [videorecording (DVD)] - Dench, Judi, 1934-; Smith, Maggie, 1934-; Patel, Dev, 1990-; Gere, Richard, 1949- (20th Century Fox Home Entertainment, 2015)
As the Best Exotic Marigold Hotel has only a single remaining vacancy - posing a rooming predicament for two fresh arrivals - Sonny pursues his expansionist dream of opening a second hotel.